2011
DOI: 10.1111/j.1747-0285.2011.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Crystal Structure of Bone Marrow Kinase in the X Chromosome: A Tec Family Kinase

Abstract: Bone marrow kinase in the X chromosome, a member of the Tec family of tyrosine kinases, plays a role in both monocyte ⁄ macrophage trafficking as well as cytokine secretion. Although the structures of Tec family kinases Bruton's tyrosine kinase and IL-2-inducible T-cell kinase are known, the crystal structures of other Tec family kinases have remained elusive. We report the X-ray crystal structures of bone marrow kinase in the X chromosome in complex with dasatinib at 2.4 Å resolution and PP2 at 1.9 Å resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…We also simulated conformational dynamics of Dasatinib binding using crystal structures of Dasatinib complexes with ABL [23], SRC [40], LYN [41], EPHA4 [42], BMX [43], and BTK [44], and P38 kinases. The projection of MD trajectories onto the essential space of low frequency modes revealed characteristic similarities in the distribution of structurally rigid and conformationally flexible regions of the kinase core (S1 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also simulated conformational dynamics of Dasatinib binding using crystal structures of Dasatinib complexes with ABL [23], SRC [40], LYN [41], EPHA4 [42], BMX [43], and BTK [44], and P38 kinases. The projection of MD trajectories onto the essential space of low frequency modes revealed characteristic similarities in the distribution of structurally rigid and conformationally flexible regions of the kinase core (S1 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale profiling studies have revealed a significant promiscuity of Dasatinib that can target over 30 different tyrosine and Ser/Thr kinases [3539]. Crystal structures of Dasatinib complexes with ABL [23], SRC [40], LYN [41], EPHA4 [42], BMX [43], and BTK kinases [44] have supported the notion that functional promiscuity of this inhibitor may be associated with conformational tolerance to multiple kinase forms. Structural plasticity of protein kinase conformations in complexes with Dasatinib ranged from fully active DFG-in states (in ABL, SRC, LYN, EPHA4, and BTK kinases) to an inactive DFG-out conformation of BMX [43], and an intermediate DFG-out form of BTK kinase [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Boc protecting group from the coupled amino acid derivatives was removed in the presence of para-toluenesulfonic acid (pTsOH) in acetonitrile. The crude products were purified by flash silica gel columnc hromatography.A ll synthesized compounds were characterized by 1 Ha nd 13 CNMR spectroscopy and high-resolution time-of-flight electrospray mass spectrometry.T he purity of final products (! 95 %) was confirmed by reversed-phasea nalytical HPLC.…”
Section: Chemistrymentioning
confidence: 99%
“…[5] It has also been crystallized as ab ound ligand to Abl, BMX, BTK, EphA4,L yn, p38a,p 38MAP,a nd Src kinases. [7][8][9][10][11][12][13][14] The common manner by which it binds to each of thesek inases suggestsi t should be similar for many other kinases as well. This may,i n part, explain the sidee ffects of the compound at clinical dosage.…”
Section: Introductionmentioning
confidence: 99%